STUDY OF INFRASTRUCTURE FACILITIES IN PRIMARY SCHOOLS DUE TO SARVA SHIKSHA ABHIYAN - Kumar, Murari; Singh, Dharmendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Since independence, continuous efforts are being made for the development of primary education. So that the goal of universalization of education can be achieved. Many schemes and programs have been implemented for its development. In this sequence, to achieve the goal of universalization, the Sarva Shiksha Abhiyan program in 2001 is a latest initiative in this direction. This program is a time-bound plan for universalization of primary education and providing quality education. Which is being operated through the center, state and local bodies. In which, with useful and meaningful primary education, social, regional and gender inequality is to be eliminated with the active participation of the community and universal retention of children in school is to be ensured. The focus of this scheme is mainly rural areas. Many facilities are being provided so that everyone can get education.